(untitled) (Fiep Bulletin - online, 2015)
Interrelationships between selected physical variables and achivements of college women. By C. Arnett. Effects of eating at various times on subsequent performances in the one-mile freestyle swim. By G. Asprey, L. Alley and W. Tuttle. Pulmonary function changes which accompany athletic conditioning programs: by J. Bachman.